Características maternas e neonatais relacionadas ao óbito em recém-nascidos com cardiopatia congênita - Sousa, Marilia Cordeiro de (2017)
All over the world, in several regions, the congenital anomalies have stood out as one of the main causes of death in their first year of life, specially in the newborn period. Among these anomalies, congenital cadiopathies, with a prevalence of 8:1000 live births. This study aimed to analyse newborn and maternal characteristics related to newborn deaths with congenital cardiopathy. It is a transversal, retrospective study with a quantitative approach. For that purpuse, it was used secondary collected data from puerperal and their live newborn children patient records diagnosed with congenital cardiopathies in a Public Hospital in Goiania, Goias State, Brazil, from 2005 to 2015. It was included 43 newborn children diagnosed with congenital cardiopathies which fit the criteria adopted, including diagnosis by post-natal echocardiogram. Considering the sociodemographic maternal variables, 63% were from 15 to 35 years old, 63% were from Goias State countryside, 35% had 8 years or less of formal education, 40% were in a relationship and 37% were unnemployed. Among the obstetric variables, the mothers who had more than one child were 60%, 44% had live births, 79% had cesarean sections, 91% were single pregnancy and 46% had less than 6 pre-natal consults. The average number of pre-natal consults was 2/2,5. Considering the neonatal variables of the newborn children who had congenital cardiopathies, most of them were female (54%), 51% had Apgar & or below in the first minute and 51% had Apgar 7 or above in the fifth minute; 93% had complications in birth and 56% had related congenital anomalies (specially Down Syndrome). The gestational age for the 43 pregnancies varied between 34,3 to 38,1 weeks. The newborns weight varied from 700g to 5.410g, average 2.598g ± 134,5g. 81% of the newborns had acyanotic congenital cardiopathies while only 19% of them had the cianotic type (8 cases). The general mortality rate was 39,5%, i.e., 17 deaths. Acyanotic congenital cardiopathies were responsible for 11 deaths (65%), while the cyanotic ones were responsible for 6 deaths (35%). The avegare of living days before death was 8,5 ± 1 days during the early neonatal period. It was observed that the death by congenital cardiopathy showed significant difference in relation to the maternal variables: parity (0,014) and type of pregnancy (0,025), multiple pregnancies and single gestation, respectively. And there was also an association estatistically significant between neonatal death and cyanotic congenital cardiopathy (0,045). It is concluded that congenital cardiopathies are more prevalent in young women, from the countryside, who had more than one child, with single gestation, being the death more common in newborn children with cyanotic congenital cardiopathies. Therefore, the reduction of death by congenital cardiopathy depends on high quality pré-natal care, early diagnosis and post-natal timely intervention.